Adenovirus Keratoconyunctivity - Kurbanov Sherdon Karshievich (Zien Journals, 2022)
Inflammatory diseases of the conjunctiva have been the main cause of general autumn diseases. About 40% of patients who seek medical help for conjunctivitis in autumn are patients with adenoviral conjunctivitis. Adenovirus conjunctivitis, which develops into a chronic form without proper treatment, leads to social problems by lowering the work rate of the population, especially the able-bodied. If the disease is not treated in time, the quality of life of patients will decline.
Keywords: conjunctivitis; adenovirus; bacterial conjunctivitis; epidemic keratoconjunctivitis